Classification of human meningiomas: lights, shadows, and future perspectives. Issue 12 (4th July 2016) - Barresi, Valeria; Caffo, Maria; Tuccari, Giovanni
Abstract : Meningiomas represent the most common primary tumors of the central nervous system (CNS) in adulthood. They are currently classified into several histotypes and into three grades of malignancy according to the criteria of the World Health Organization (WHO) classification of tumors of the CNS. WHO histological grade is currently the most significant morphological predictor of recurrence risk of meningiomas. For this reason, it is fully taken into consideration in postsurgical therapeutic decision making in patients with meningioma. However, the main drawback of the WHO grading system system is that criteria for its assessment are rather subjective and poorly standardized. Hence, additional factors are warranted to predict recurrence risk of meningiomas, so that patients may actually receive the most appropriate therapy. In recent years, biomolecular pathogenesis of meningiomas has been partially clarified, and many efforts have been made in the identification of molecular factors associated with recurrence risk of meningioma. Here we review WHO criteria currently used for classification of meningiomas and discuss on pitfalls and limits of grading assessment. In addition we present the latest advancement in the knowledge of biomolecular alterations involved in the pathogenesis and progression of meningiomas. Similarly to what has already happened for gliomas, a novel classification integrating histology and molecular information might overcome the limits of histological classification in terms of reproducibility as well as of prognostic and predictive relevance. © 2016 Wiley Periodicals, Inc. Abstract : Meningiomas are currently subdivided into 13 histotypes and three histological grades of malignancy with increasing recurrence risk. However, this classification may show low reproducibility. Recent findings suggest that meningiomas may be classified on molecular profile and that recurrence risk may be better predicted by the mutational status of TERT promoter.